2022
DOI: 10.1136/bmjopen-2021-054669
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of venous thrombotic events and events of special interest in a retrospective cohort of commercially insured US patients

Abstract: ObjectiveTo estimate the US incidence of thrombotic events and related rare diagnoses.DesignClaims-based retrospective cohort study of incidence.SettingUS commercial health insurance administrative claims database.ParticipantsAdults 25–64 years of age between 2015 and 2019 with a minimum of 12 consecutive thrombosis-free months of continuous enrolment beginning 2014 were selected.Main outcomesAge (10-year intervals) and sex stratum-specific incidence rates per 100 000 person-years were determined for venous th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…It may be explained by the rapidly aging population and higher prevalence of cardiovascular disease and cancer. However, most studies demonstrated the incidence of women during childbearing ages of 20–40 is higher than that in men [ 14 , 15 ], and the over 13 million enrollees from the USA for the 5-year pre-pandemic period (2015–2019) indicates that VTE incidence tended to increase with age and was higher for women under 55 [ 16 ]. However, VTE can be prevented in clinical practice, and it is of great significance to screen high-risk population for VTE.…”
Section: Epidemiologymentioning
confidence: 99%
“…It may be explained by the rapidly aging population and higher prevalence of cardiovascular disease and cancer. However, most studies demonstrated the incidence of women during childbearing ages of 20–40 is higher than that in men [ 14 , 15 ], and the over 13 million enrollees from the USA for the 5-year pre-pandemic period (2015–2019) indicates that VTE incidence tended to increase with age and was higher for women under 55 [ 16 ]. However, VTE can be prevented in clinical practice, and it is of great significance to screen high-risk population for VTE.…”
Section: Epidemiologymentioning
confidence: 99%
“…From the base cohort of women, 20,359 incident cases of acute VTE met inclusion criteria and were matched with 203,590 controls (Figure 1). Among cases, 76% were primary diagnoses, 89.37% (18,194) 1).…”
Section: Samplementioning
confidence: 99%
“…For example, dydrogesterone, a lower risk progestin, is unavailable and US incidence of VTE is much higher than in Europe. [18] The WHI and HERS results vastly reduced use of MHT, [14][15][16] but approximately eight percent of US women 50 and older continue to use non-contraceptive estrogens, [16] and little data exist as to how many additional women in this age range use hormonal contraceptives. Common indications for MHT include hot flashes, vaginal dryness, disruptions in sleep patterns, and inability to concentrate.…”
Section: Hormone Exposure and Venous Thromboembolism In Commercially-...mentioning
confidence: 99%
See 2 more Smart Citations